Arginase-1-specific T cells target and modulate tumor-associated macrophages - Mads Hald Andersen; Inés Lecoq; Ayako Wakatsuki Pedersen; Evelina Martinenaite; Shamaila Munir Ahmad; Maria Perez-Penco; Lucia Lara de la Torre; Marion Chapellier; Lars Rønn Olsen; Mia Aaboe-Jørgensen; Hannah Jorinde Glöckner; Anne Mette Askehøj Rømer (Journal for ImmunoTherapy of Cancer)
Background Arginase-1 (Arg1) expressing tumor-associated macrophages (TAMs) may create an immune-suppressive tumor microenvironment (TME), which is a significant challenge for cancer immunotherapy. We previously reported the existence of Arg1-specific memory T cells among peripheral blood mononuclear cells (PBMCs) and described that Arg-1-based immune modulatory vaccines (IMVs) control tumor growth and alter the M1/M2 macrophage ratio in murine models of cancer. In the present study, we investigated how Arg1-specific T cells can directly target TAMs and influence their polarization.Methods Murine Arg1-specific CD4+T cells isolated from splenocytes of animals vaccinated with an Arg1-derived peptide in the adjuvant montanide were co-cultured with either in vitro M2-differentiated bone marrow-derived macrophages or ex vivo isolated F4/80+TAMs. Human Arg1-specific CD4+T cell clones were co-cultured with Arg1-expressing TAMs generated in vitro from either PBMC-derived CD14+cells or the myeloid cell lines MonoMac1 and THP-1. MHC class II-restricted Arg-1 peptide presentation by macrophages was confirmed by immunopeptidomics. T-cell-mediated changes in the macrophage immune phenotype and cytokine microenvironment were examined using flow cytometry, RT-qPCR and multiplex immunoassay. The effect of Arg1-derived peptide IMV on TAMs in vivo was assessed by multiplex gene analysis of F4/80+cells.Results We show that Arg1-based IMV-mediated tumor control was linked to a decrease in multiple immunosuppressive pathways in the TAM population of the treated animals. Tumor-conditioned media (TCM) derived from Arg1-vaccinated mice induced significantly higher upregulation of MHC-II on exposed myeloid cells compared with controls. Furthermore, murine CD4+Arg1-specific T cells were able to target TAMs and effectively reprogram their phenotype ex vivo by secreting IL2 and IFNγ. Next, we established that human Arg1+TAMs present Arg1-derived peptides and are directly recognized by proinflammatory CD4+Arg1-specific T cell clones. These CD4+Arg1-specific T cells were able to reprogram TCM-conditioned macrophages as observed by increased expression of CD80 and HLA-DR.Conclusions TAMs may be directly targeted and modulated by Arg1-specific CD4+T cells. These findings provide a strong rationale for future clinical development of Arg1-based IMVs to alter the immune-suppressive TME by reprogramming TAMs and promoting a proinflammatory TME.